The faith once delivered: essays in honor of Dr. Wayne R. Spear - Selvaggio, Anthony T.; Spear, Wayne R. ca. 20./21. Jh. (The Westminster Assembly and the reformed faith, 2007)
The vitality of reformed systematic theology / Richard B. Gaffin, Jr. -- A tract for the times : James Buchanan's the doctrine of justification in historical and theological context / Carl R. Trueman -- Transforming power and comfort : the Puritans on adoption / Joel R. Beeke -- The benefits of Christ : double justification in Protestant theology before the Westminster Assembly / R. Scott Clark -- From popery to principle : covenanters and the kingship of Christ / David McKay -- Good and necessary consequence in the Westminster confession / C.J. Williams -- The Lord's day and the Westminster confession / Rowland S. Ward -- Unity or disunity : covenant theology from Calvin to Westminster / Anthony T. Selvaggio -- The doctrine of the atonement from the Westminster Assembly to the twentieth century / Richard C. Gamble -- The use and abuse of Christian liberty / D.G. Hart